2006
DOI: 10.1080/14616740500415490
|View full text |Cite
|
Sign up to set email alerts
|

Bringing nations in: Some methodological and conceptual issues in connecting feminisms with nationhood and nationalisms

Abstract: The recent explosion of case studies about women's involvements in national projects reveals considerable diversity ranging from hostility and alienation, to affiliation or participation. Feminist analysis is just starting to explore the causes and effects of such diversity, however, since a single, common relationship usually was theorized between 'gender' and 'nation'. This article addresses some methodological and conceptual issues concerning the systematic comparison of these diverse relationships. It is a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(20 citation statements)
references
References 18 publications
1
18
1
Order By: Relevance
“…Compared to other parties in parliament, radical right parties together with the ethnic Turkish party MRF are those that consistently include the smallest number of women in their parliamentary groups, apart from small parties that make a brief appearance. This finding is consistent with previous research arguing that nationalist and ethnic parties tend to include fewer women (Vickers 2006;Yuval-Davis 1997). By comparison, the current ruling party GERB has had over 33% female MPs in the last two parliaments.…”
Section: How Many Women? Descriptive Representation In Bulgaria's Prrsupporting
confidence: 82%
“…Compared to other parties in parliament, radical right parties together with the ethnic Turkish party MRF are those that consistently include the smallest number of women in their parliamentary groups, apart from small parties that make a brief appearance. This finding is consistent with previous research arguing that nationalist and ethnic parties tend to include fewer women (Vickers 2006;Yuval-Davis 1997). By comparison, the current ruling party GERB has had over 33% female MPs in the last two parliaments.…”
Section: How Many Women? Descriptive Representation In Bulgaria's Prrsupporting
confidence: 82%
“…It is also the case within women"s studies and feminist journals. This is not to deny, of course, that methodological debate within feminism does occur (see, for example, Bacchi, 2005: Eveline et al, 2009Fonow and Cook, 2005;Henry, 2007;Power, 2004;McCall, 2005: Vickers, 2006. However, our findings suggest that in empirical articles where methodological justifications are given they refer predominantly to technical rather than epistemological issues.…”
contrasting
confidence: 50%
“…Contributors to IFjP have illuminated the tensions between the putatively inclusive language of nationalism and the raced-gendered hierarchies that mediate inclusion (Banerjee 2006;Das 2006;Vickers 2006). In an investigation of gender and nationalism in Israel, for example, Tami Jacoby (1999: 398) demonstrated that despite the persistence of egalitarian rhetoric, women tended to be 'included in nation building on the basis of their familial and biological functions as mothers of soldiers and ideological appendages of male leaders and fighters'.…”
Section: Borrowings That Enable New Modes Of Thoughtmentioning
confidence: 97%